STUDIES ON MANAGEMENT OF BOLLWORMS USING DIFFERENT INTEGRATED PEST MANAGEMENT STRATEGIES IN COTTON - S. NAGENDRA (International Journal of Pharma and Bio Sciences, 2015)
This investigation was aimed to study the management of bollworms using different integrated pest management strategies in cotton. Highest infestation in bolls at harvest was recorded in module-5 and lowest was recorded in module-2. Net returns were highest in module-5, which also recorded maximum cost-benefit ratio. Low net returns and cost-benefit ratio were recorded in module-3. Eventhough, seed cotton yield was recorded maximum in module-6 where combinations of different biopesticides and conventional chemical insecticides were used, the net returns and cost-benefit ratios were highest in module-5 where Setaria sp. was intercropped with cotton and cultural practices were practiced to manage the bollworm infestation along with use of bioagents and biopesticides. Thus, it can be concluded that module-5 comprising of mixed cropping with Setaria, 5% neem seed kernel extract spray, mechanical control of large size larvae, two releases of Trichogramma, Helicoverpa armigera nucleopolyhedrosis virus and Bacillus thuringinesis spray at economic threshold level can be adopted as an effective IPM module in cotton.